Both central sympathoexcitation and peripheral angiotensin II-dependent vasoconstriction contribute to hypertension development in immature heterozygous Ren-2 transgenic rats - Řezáčová, Lenka; Vaněčková, Ivana; Hojná, Silvie; Vavřínová, Anna; Valovič, Pavol; Rauchová, Hana; Behuliak, Michal; Zicha, Josef (Hypertension research, 2022)
Recently, we demonstrated that chronic blockade of the renin-angiotensin system (RAS) lowered the blood pressure (BP) of adult Ren-2 transgenic rats (TGR) mainly through the attenuation of central sympathoexcitation. However, the participation of central and peripheral mechanisms in the development of high BP in immature TGR remains unclear. In the present study, 6-week-old heterozygous TGR males were chronically treated with intracerebroventricular (ICV) or intraperitoneal (IP) infusions of the AT1 receptor inhibitor losartan (1 or 2 mg/kg/day) for 4 weeks. The influence of these treatments on sympathetic- and angiotensin II-dependent BP components (BP response to pentolinium or captopril, respectively) as well as on BP response to exogenous angiotensin II were determined to evaluate the participation of central and peripheral RAS in hypertension development. Chronic IP losartan administration (1 or 2 mg/kg/day) lowered the BP of immature TGR by reducing both sympathetic and angiotensin II-dependent BP components. The central action of IP-administered losartan was indicated by a reduced BP response to acute ICV angiotensin II injection. Chronic ICV administration of a lower losartan dose (1 mg/kg/day) reduced only the sympathetic BP component, whereas a higher ICV administered dose (2 mg/kg/day) was required to influence the angiotensin II-dependent BP component. Accordingly, chronic ICV losartan administration of 2 mg/kg/day (but not 1 mg/kg/day) attenuated the BP response to acute intravenous angiotensin II application. In conclusion, central sympathoexcitation seems to play an important role in hypertension development in immature TGR. Central sympathoexcitation is highly susceptible to inhibition by low doses of RAS-blocking agents, whereas higher doses also affect peripheral angiotensin II-dependent vasoconstriction.
Keywords: Angiotensin II; potkani transgenní; Male; hypertenze; angiotensin II; hypertension; losartan; intracerebroventricular; mužské pohlaví; Hypertension; Vasoconstriction; Rats, Transgenic; krysa rodu Rattus; Ren-2 transgenic rats; Animals; krevní tlak; renin-angiotensin systém; Renin; zvířata; Renin-Angiotensin System; Rats; Blood Pressure; vazokonstrikce; renin; Losartan